Contrast-enhanced spectral mammography in patients with MRI contraindications. (July 2018) - Richter, Vivien; Hatterman, Valerie; Preibsch, Heike; Bahrs, Sonja D; Hahn, Markus; Nikolaou, Konstantin; Wiesinger, Benjamin
Background: Contrast-enhanced spectral mammography (CESM) is a novel breast imaging technique providing comparable diagnostic accuracy to breast magnetic resonance imaging (MRI). Purpose: To show that CESM in patients with MRI contraindications is feasible, accurate, and useful as a problem-solving tool, and to highlight its limitations. Material and Methods: A total of 118 patients with MRI contraindications were examined by CESM. Histology was obtained in 94 lesions and used as gold standard for diagnostic accuracy calculations. Imaging data were reviewed retrospectively for feasibility, accuracy, and technical problems. The diagnostic yield of CESM as a problem-solving tool and for therapy response evaluation was reviewed separately. Results: CESM was more accurate than mammography (MG) for lesion categorization (r = 0.731, P  < 0.0001 vs. r = 0.279, P  = 0.006) and for lesion size estimation (r = 0.738 vs. r = 0.689, P  < 0.0001). Negative predictive value of CESM was significantly higher than of MG (85.71% vs. 30.77%, P  < 0.0001). When used for problem-solving, CESM changed patient management in 2/8 (25%) cases. Superposition artifacts and timing problems affected diagnostic utility in 3/118 (2.5%) patients. Conclusion: CESM is a feasible and accurate alternative for patients with MRI contraindications, but it is necessary to be aware of the method's technical limitations.